Efficacy and safety of a millimetre wave medical device for pain neuromodulation in peripheral osteoarthritis: a crossover randomised trial - Maindet, Caroline; Giai, Joris; Leroy, Corentin; Proust, Marion; Lalami, Gilliane; Boudry, Isabelle; Thiers, Marlène; Bosson, Jean-Luc; Grange, Laurent (Rheumatology (Oxford, England), 2025)
To manage osteoarthritis (OA)-related pain, current guidelines recommend a combination of non-pharmacological and pharmacological treatments. The objective of this study was to assess a millimetre-wave-emitting medical device (MD) for neuromodulation of pain in patients with peripheral OA. In this monocentric, prospective, crossover, randomised controlled trial, 60 patients with peripheral OA affecting joints (ankle, knee, hip, shoulder, elbow, and fingers) and a pain score ≥ 4 on the Visual Analogue Scale (VAS) were recruited and randomly assigned to one of two crossover sequences. The primary outcome was self-assessed pain, while secondary outcomes included life and sleep quality. Of the 60 patients included, 31 were randomly assigned to the OFF/ON sequence and 29 to the ON/OFF sequence. The baseline mean pain scores for the groups was 6.05 (SD = 1.36) and 6.31 (SD = 1.52) on the VAS, respectively. During the MD use period, the mean daily VAS pain score was 4.57 (SD = 2), compared with 5.32 (SD = 1.77) during the period without MD use. The mean paired difference between periods was 0.74 (SD = 1.77). This difference was statistically significant (p= 0.002). The corresponding effect size was 0.42. No carryover, sequence, or period effects were observed. Secondary outcomes related to quality of life and sleep quality showed significant improvement with MD use. No serious adverse events were reported. In patients with peripheral OA, regular use of this MD significantly reduced in pain (VAS), improved both quality of life (EQ5D-5L) and sleep quality (VAS). Future research should focus on individualised benefit-risk balance, incorporating patient preferences. ClinicalTrials.gov; NCT04590079.